2009
DOI: 10.1182/blood-2009-07-192740
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia: interplay between noncoding RNAs and protein-coding genes

Abstract: One of the most unexpected and fascinating discoveries in oncology over the past few years is the interplay between abnormalities in protein-coding genes and noncoding RNAs (ncRNAs) that is causally involved in cancer initiation, progression, and dissemination. MicroRNAs (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 90 publications
(111 reference statements)
0
90
0
5
Order By: Relevance
“…MiRNAs act post-transcriptionally within cells to regulate gene expression by binding to target messenger RNAs (mRNAs), causing either translation repression or cleavage of target transcripts. 38 Using bioinformatic analysis, Katzaki et al found that 4 out of 9 patients with overlapping deletions of 21q22 had a deletion of the miRNA miR-802. 34 However, 2 of the patients who developed MDS/AML were included in the analysis and both retained expression of miR-802.…”
Section: Syndromic Cases Of Loss Of Chromosome 21q22mentioning
confidence: 99%
“…MiRNAs act post-transcriptionally within cells to regulate gene expression by binding to target messenger RNAs (mRNAs), causing either translation repression or cleavage of target transcripts. 38 Using bioinformatic analysis, Katzaki et al found that 4 out of 9 patients with overlapping deletions of 21q22 had a deletion of the miRNA miR-802. 34 However, 2 of the patients who developed MDS/AML were included in the analysis and both retained expression of miR-802.…”
Section: Syndromic Cases Of Loss Of Chromosome 21q22mentioning
confidence: 99%
“…A generally accepted sequence of steps for the biochemical processing of precursor miRNA to the mature forms is known as the ''linear" canonical pathway (Winter et al, 2009). MiRNAs have been found to play particular important roles in cell differentiation by negatively regulating translation (Calin & Croce, 2009;Iorio & Croce, 2009;Lim et al, 2005;Liu & Olson, 2010). miRNAs bind to specific 3'UTR sequences of mRNAs and thereby prevent efficient translation or mediate degradation of target mRNAs.…”
Section: Microrna-21 (Mir-21)mentioning
confidence: 99%
“…Recently, several studies have revealed a critical role for microRNAs (miRNAs) during tumorigenesis and metastasis of several cancers, including MB. [3][4][5][6] Besides intracellular miRNAs with the traditional function of translation regulation, there is accumulating evidence that miRNAs exist extracellularly in body fl uids, including cerebrospinal fl uids (CSF). [7,8] Several reports have described that deregulated extracellular-miRNAs (ex-miRNAs) are closely associated with the clinical course of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%